Comparative Performance Evaluation of Modified Passive Solar Still Using Sensible Heat Storage Material and Increased Frontal Height. (2016) - Patel, Pinakeen; Kumar, Rajesh
Abstract: This paper represents experimental results of modified passive solar stills. There are three different Models have been developed in which first still having Thermic fluids (HP-500) as sensible heat storage material, Second with increased Frontal Height and Third one was conventional Still, having same basin area of 76 X 76 cm 2 . A comparison study between the modified still and conventional still was carried out to evaluate the distillation and effective parameters under the same climate conditions for continuous nine days with different depth of water (2 cm, 3 cm and 4 cm). The effect of sensible heat storage material, Depth of water and Front height of solar still have been investigated to compare the performance of passive single slop solar still. The result indicate that for a temperature difference of 17°-19° C between oil and basin water the productivity of heat storage solar still is better than the conventional solar still. For low solar radiation the still which have less front height (10 cm) showed significant productivity than that of 15 cm height solar still. For 2 cm water depth, productivity for still containing Thermic Fluid and Increased Frontal height increased by 11.24% and 23% respectively, as compared to conventional still. For 3 cm water depth, productivity for still containing Thermic Fluid is decreased by 18% and for still with Increased Frontal height productivity increased by 18%, as compared with conventional still. For 4 cm water depth, productivity for still containing Thermic Fluid is decreased by 30% and for still with Increased Frontal height increased by 2%.